ACC GABA levels are associated with functional activation and connectivity in the fronto-striatal network during interference inhibition in patients with borderline personality disorder - Wang, Guo-Ying; Eijk, Julia Maria van; Demirakça, Traute; Sack, Markus; Krause-Utz, Annegret; Cackowski, Sylvia; Schmahl, Christian; Ende, Gabriele (NeuroImage, 2017)
Impulsivity often develops from disturbed inhibitory control, a function mainly regulated by γ-Aminobutyric acid (GABA) levels in the anterior cingulate cortex (ACC) and the fronto-striatal system. In this study, we combined MRS GABA measurements and fMRI to investigate neurochemical and neurofunctional correlates of interference inhibition, further emphasizing the direct relationship between those two systems, as well as their relations to impulsivity in patients with BPD. In addition to BOLD activation, task-dependent functional connectivity was assessed by a generalized psychophysiological interactions approach. Full factorial analyses were performed via SPM to examine the main effect (within-group associations) as well as the interaction term (group differences in the association slope). The UPPS scales were used to evaluate impulsivity traits. Compared to healthy controls (HCs), BPD patients exhibited significantly less ACC-caudate functional connectivity during interference inhibition. ACC GABA levels in BPD patients but not in HCs were positively related to the magnitude of activation in several fronto-striatal regions (e.g. ACC, frontal regions, putamen, caudate,) and the strength of ACC-caudate functional connectivity during interference inhibition. The strength of the correlations of GABA with connectivity significantly differs between the two groups. Moreover, among all the UPPS impulsivity subscales, UPPS sensation seeking in the BPD group was related to GABA and was also negatively related to the task-dependent BOLD activation and functional connectivity in the fronto-striatal network. Finally, mediation analyses revealed that the magnitude of activation in the caudate and the strength of ACC-caudate functional connectivity mediated the relationship between ACC GABA levels and UPPS sensation seeking in patients with BPD. Our findings suggest a disconnectivity of the fronto-striatal network in BPD patients during interference inhibition, particularly for patients with higher impulsivity. The ACC GABAergic system seems to play a crucial role in regulating regional BOLD activations and functional connectivity in this network, which are further associated with impulsive sensation seeking in BPD.